In Vitro Study of Antibacterial Activity of Î³- irradiated and Unirradiated Leguminous Seed Coats - CHIKANE, M. R. (International Journal of Pharmaceutical & Biological Archive, 2010)
Antimicrobial activity of seed coats contents of Vigna Mungo, Cajanus Cajan and Vigna Unguiculata was evaluated against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis and Klebsiella pneumonia.Gamma irradiated and unirradiated seed coats extracts were screened for antibacterial activity, which involved the determination of inhibition zone in mm. Norfloxacin was used as standared reference. Gamma unirradiated seed coat extracts showed a high antibacterial activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aerunginosa Bacillus Subtilis and Klebsiella pneumonia as compared to gamma irradiated seed coats extracts.